2005
DOI: 10.1158/0008-5472.can-05-0654
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Sensitizes Tumor Cells to Dendritic Cell–Mediated Apoptosis, Uptake, and Cross-Presentation

Abstract: Dendritic cells are professional antigen-presenting cells associated with efficient antigen processing and presentation to T cells. However, recent evidence also suggests that dendritic cells may mediate direct tumoricidal functions. In this study, we investigated the mechanism by which murine dendritic cells mediate the apoptotic death of murine lymphoma cell lines, and whether dendritic cell effector function could be enhanced by preconditioning tumor cells with the protein phosphatase inhibitor nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 43 publications
1
44
1
Order By: Relevance
“…144 Taken together, these emerging data suggest that different DC subsets may have both tumor-promoting as well as tumor-suppressive properties in vivo. This can be exemplified by the demonstration that breast cancer instructs DCs to induce CD4 þ T cells secreting IL13 and promote cancer development by mediating DC polariziation.…”
Section: Interactions Of Dcs With Living Tumor Cellsmentioning
confidence: 94%
“…144 Taken together, these emerging data suggest that different DC subsets may have both tumor-promoting as well as tumor-suppressive properties in vivo. This can be exemplified by the demonstration that breast cancer instructs DCs to induce CD4 þ T cells secreting IL13 and promote cancer development by mediating DC polariziation.…”
Section: Interactions Of Dcs With Living Tumor Cellsmentioning
confidence: 94%
“…72,73 Immature DCs have also been shown to kill freshly isolated tumors. [74][75][76] Although in vitro-derived immature DCs kill target cells very efficiently at low effector/target ratios via an apoptotic mechanism involving DNA fragmentation, mitochondrial dysfunction, and late membrane disruption, the level of cytotoxicity found in the freshly isolated, immature DCs remains low and questionable. 75 To note, while Chen's group 70 demonstrated that the tumor killing by immature DCs is mediated through direct cell-to-cell contact, Vujanovic's group 75 showed, using the same type of immature DCs, that the killing mechanism was mediated by both cell-to-cell contact and soluble mediators.…”
Section: Killer Dcsmentioning
confidence: 99%
“…It is believed that CD40L-induced robust TNF-a secretion exerts a differential effect on target cell death according to the balance of pro-apoptotic signals/ pro-NF-kB signals. Huang et al 74 recently reported that bone marrow-derived DCs mediate cytotoxic activity toward B-cell lymphoma. Interestingly, they showed that by disrupting the balance of pro-apoptotic versus anti-apoptotic signals, target cells can be sensitized to TNF family ligand-mediated apoptosis.…”
Section: Killer Dcsmentioning
confidence: 99%
“…Indeed, the NO-dependency of KDC lysis observed by Srivastava et al 9 may reflect the reported ability of NO to sensitize tumor cell targets to apoptosis mediated by KDC via Fas, etc. 13 …”
Section: -25mentioning
confidence: 99%
“…Interestingly, it appears that such in vitro generated DC exhibit most potent cytotoxic potential after undergoing 'spontaneous' maturation (occurring over time in the absence of known exogenous activators). 13 TNF family members including FasL, TRAIL and TNF-a are expressed by cultured immature and spontaneously-matured BM-DC, 4,13 allowing these KDC to promote the apoptosis of human Jurkat cells and the murine A20 B cell lymphoma, with Fas-L (-/-) DC proving inferior in KDC function. 13 Furthermore, transduction of BM-DC with adenovirus constructs encoding mIL-12p70 and mIL-18 leads to enhanced TNF-a and TRAIL expression and improved KDC function against syngenic CMS4 sarcoma cells.…”
Section: Cultured Kdc Generated From Bone Marrow Progenitor Cells or mentioning
confidence: 99%